ATG16L1 negatively regulates RICK/RIP2-mediated innate immune responses. (10th September 2020) - Honjo, Hajime; Watanabe, Tomohiro; Arai, Yasuyuki; Kamata, Ken; Minaga, Kosuke; Komeda, Yoriaki; Yamashita, Kouhei; Kudo, Masatoshi
Abstract: Polymorphisms in the autophagy-related protein 16 like 1 ( ATG16L1 ) and nucleotide-binding oligomerization domain 2 ( NOD2 ) genes are associated with Crohn's disease (CD). Impaired interaction between ATG16L1 and NOD2 underlies CD immunopathogenesis. Although activation of the receptor-interacting serine–threonine kinase (RICK, also known as RIP2), a downstream signaling molecule for NOD2 and multiple toll-like receptors (TLRs), plays a pathogenic role in the development of inflammatory bowel disease, the molecular interaction between ATG16L1 and RICK/RIP2 remains poorly understood. In this study, we examined the physical interaction between ATG16L1 and RICK/RIP2 in human embryonic kidney 293 cells and human monocyte-derived dendritic cells (DCs) expressing excessive and endogenous levels of these proteins, respectively. We established that ATG16L1 binds to RICK/RIP2 kinase domain and negatively regulates TLR2-mediated nuclear factor-kappa B (NF-κB) activation and pro-inflammatory cytokine responses by inhibiting the interaction between TLR2 and RICK/RIP2. Binding of ATG16L1 to RICK/RIP2 suppressed NF-κB activation by down-regulating RICK/RIP2 polyubiquitination. Notably, the percentage of colonic DCs expressing ATG16L1 inversely correlated with IL-6 and TNF-α expression levels in the colon of CD patients. These data suggest that the interaction between ATG16L1 and RICK/RIP2 maintains intestinal homeostasis via the down-regulation of TLR-mediated pro-inflammatory cytokine responses. Abstract : ATG16L1 inhibits RICK-TLR2 interactions and intestinal inflammation